The level of excessive emotional style among children with autism from the point of view of their teachers (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The current research aims to identify the level of  and excessive emotional style in children with autism from the point of view of their teachers, sample consisted of the search of  (105) parameter of all the centers of autism in the province of Dhi Qar and the center of the province of Babylon , chosen by way of random , considered the nature of the Research adopted by a Researcher of the descriptive approach , and to achieve the objectives of the research prepared by T researcher of the scale of the abuse of a component (3 0) paragraph , distributed on (6) areas are: (flexibility, expectations, self - awareness, social intuition, sensitivity to context, attention) was Verification of the validity and reliability of the scale , and the statistical analysis package has been approved  (spssTo extract the results, the results showed: The results of the research showed that the excessive emotional style was greater than the theoretical mean and statistically significant, and the researcher attributes that to the fact that disabled children in general and the autistic child in particular enjoy excessive emotion as a result of rejection and neglect that this group of children are exposed to, so the child clings to the one who provides him with care and excessive attention. The variable method of emotional over the first variable covered in the study the current - limit science researcher.The recommended researcher including comes:• The necessity of holding conferences and seminars for teachers of autistic children to introduce them to theemotional style.• Awareness ofschools, including teachers and all community children's rights and the right to live a dignified life free of violence.• Theintroduction of teachers of autistic and mobile children in autism care centers with rehabilitation and development courses to provide them with the necessary skills and scientific experiences that help them in dealing with autistic children.